Leptin receptor polymorphisms and lung function decline in COPD - Hansel, N.N. (Eur Respir J, 2009)
Only a fraction of all smokers develop chronic obstructive pulmonary disease (COPD), suggesting a large role for genetic susceptibility. The leptin receptor (LEPR) is present in human lung tissue and may play a role in COPD pathogenesis. The present study examined the association between genetic variants in the LEPR gene and lung function decline in COPD. In total, 429 European Americans were randomly selected from the National Heart Lung and Blood Institute Lung Health Study. 36 single nucleotide polymorphisms (SNPs) in LEPR were genotyped using the Illumina™ GoldenGate platform (Broad Institute, Cambridge, MA, USA). Mean annual decline in forced expiratory volume in 1 s % predicted over the 5-yr period was calculated using linear regression. Linear regression models were also used to adjust for potential confounders. In addition, in vivo expression of the receptor gene was assessed with immunohistochemistry on lungs from smoke-exposed inbred mice. We identified significant associations (p<0.05) between lung function decline and 21 SNPs. Haplotype analyses confirmed several of these associations seen with individual markers. Immunohistochemistry results in inbred mice strains support a potential role of LEPR in COPD pathogenesis. We identified genetic variants in the LEPR gene significantly associated with lung function decline in a population of smokers with COPD. Our results support a role for LEPR as a novel candidate gene for COPD.